Alamat Redaksi Sekolah Pascasarjana IPB Gedung Andi Hakim Nasoetion Lt. 5, Kampus IPB Darmaga, Bogor 16680 Telp. 0251-8628448, 8622642 ext. 510 Fax. 0251-622986 e-mail: forum_pascasarjana@bima.ipb.ac.id - Dewan Editor (Forum Pasca Sarjana, 2010)
Alamat Redaksi Sekolah Pascasarjana IPB Gedung Andi Hakim Nasoetion Lt. 5, Kampus IPB Darmaga, Bogor 16680 Telp. 0251-8628448, 8622642 ext. 510 Fax. 0251-622986 e-mail: forum_pascasarjana@bima.ipb.ac.id